Campylobacteriose — eine zoonotische Infektionskrankheit - Alter, Thomas; Bereswill, Stefan; Backert, Steffen (BioSpektrum, 2021)
Campylobacter jejuni represents an important zoonotic pathogen that is causing foodborne enteric infections. In the human gut, C. jejuni bacteria induce intestinal campylobacteriosis which can develop into systemic post-infectious sequelae such as Guillain-Barré syndrome or rheumatoid arthritis. Here, we review the pathobiology and molecular mechanisms of C. jejuni infections as well as promising strategies to combat campylobacteriosis within the “One World — One Health” approach.
CRIS-Team Scopus Importer:2021-10-22